Intensity of reaction to tuberculoprotein is not related to severity of disease in patients with single organ vasculitis of the retina - Takkar, Brijesh; Chauhan, Ramesh Chand; Sheemar, Abhishek; Rathi, Anubha; Sinha, Priyanka; Venkatesh, Pradeep (Nepalese Journal of Ophthalmology, 2020)
Not available.